SUDAHKAH EVALUASI KEMAHIRAN BERBICARA BAHASA ARAB PADA TINGKAT DASAR DILAKUKAN? - Kholisoh, Laili Nur (Departemen Pendidikan Bahasa Arab, 2018)
Evaluation is something that is commonplace and even just flows in accordance with the calendar of education. This research aims to find out and look for a solution of the problems that occur when implementing an evaluation for Arabic speaking skills at the level of data done by observation and interviews to several Arabic language teachers at the elementary level. With the data already obtained the writer to study literature to relate some of the problems with the existing theories to find relevant solutions for each issue found. As for some of the problems found related to the evaluation of speaking skills of students at the primary level, including the following: 1) Teachers often neglect the evaluation of speaking skills for being too focused on the written evaluation, 2) time is inadequate also make teachers second priority to this evaluation, 3) Teachers admitted the difficulty to make the right instrument for the evaluation of speaking skills, and 4) the ability of students limited hamper the ongoing evaluation of speaking skills. From some of the existing problems, there are several solutions to overcome them. One was a teacher must adjust the evaluation of speaking skills are as important as some other language proficiency evaluation.Â